Automorphisms of the endomorphism semigroup of a free abelian diband - Zhuchok, Y.V. (Algebra and Discrete Mathematics, 2018)
We determine all isomorphisms between the endomorphism semigroups of free abelian dibands and prove that all automorphisms of the endomorphism semigroup of a free abelian diband are inner.